Mixotrophic Activity and Diversity of Antarctic Marine Protists in Austral Summer - Gast, Rebecca J.; Fay, Scott A.; Sanders, Robert W. (Frontiers in Marine Science, 2018)
Identifying putative mixotrophic protist species in the environment is important for understanding their behavior, with the recovery of these species in culture essential for determining the triggers of feeding, grazing rates and overall impact on bacterial standing stocks. In this project, mixotroph abundances determined using tracer ingestion in water and sea ice samples collected in the Ross Sea, Antarctica during the summer of 2011 were compared with data from the spring (Ross Sea) and fall (Arctic) to examine the impacts of bacterivory/mixotrophy. Mixotrophic nanoplankton were usually less abundant than heterotrophs, but consumed more of the bacterial standing stock per day due to relatively higher ingestion rates (1-7 bacteria mixotroph-1 h-1 vs. 0.1-4 bacteria heterotroph-1 h-1). Yet, even with these high rates observed in the Antarctic summer, mixotrophs appeared to have a smaller contribution to bacterivory than in the Antarctic spring. Additionaly, putative mixotroph taxa were identified through incubation experiments accomplished with bromodeoxyuridine labeled bacteria as food, immunoprecipitation (IP) of labeled DNA, and amplification and high throughput sequencing of the eukaryotic ribosomal V9 region. Putative mixotroph OTUs were identified in the IP samples by taxonomic similarity to known phototroph taxa. OTUs that had increased abundance in IP samples compared to the non-IP samples from both surface and chlorophyll maximum (CM) depths were considered to represent active mixotrophy and include ones taxonomically similar to Dictyocha, Gymnodinium, Pentapharsodinium and Symbiodinium. These OTUs represent target taxa for isolation and laboratory experiments on triggers for mixotrophy, to be combined with qPCR to estimate their abundance, seasonal distribution and potential impact.